Lipid monolayers at the air-water interface: A tool for understanding electrostatic interactions and rheology in bio-membranes - Wilke, Natalia (2014)
Fil: Wilke, Natalia. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Química Biológica; Argentina.